Effects of pamidronate in acute cardiotoxicity induced by doxorubicin in rats - Polegato, Bertha F. [UNESP]; Carvalho, Paula [UNESP]; Bergamasco, Carolina [UNESP]; Gonçalves, Andréa de Freitas [UNESP]; Azevedo, Paula S. [UNESP]; Modesto, Pamela [UNESP]; Roscani, Meliza Goi [UNESP]; Fernandes, Ana A. H. [UNESP]; Paiva, Sergio [UNESP]; Zornoff, Leonardo A. M. [UNESP]; Matsubara, L. S. [UNESP]; Okoshi, Marina P. [UNESP]; et al. (My University, 2015)
Aim: Evaluate pamidronate (Pam) effects in ventricular function, matrix metalloproteinase-2 (MMP-2) activity, oxidative stress, and myocardial energetic metabolism during acute doxorubicin (Dox)-induced cardiotoxicity. Methods: 64 Wistar rats were allocated in 4 groups: Control, Dox, Pam and Dox + Pam. Rats received Pam (3 mg/kg, IP) or saline. After 24 hours, rats received Dox (20 mg/kg, IP) or saline. Forty-eight hours after Dox injection, rats were euthanized. Statistical analysis: two-way ANOVA. Results: Dox induced diastolic and systolic ventricular dysfunction and increased MMP-2 activity. Dox increased myocardial oxidative stress (increased in lipid hydroperoxide, and decreased in catalase, superoxide dismutase and glutathione peroxidase myocardial levels) and impaired myocardial energetic metabolism (increased in phosphofructokinase and decreased in β-hydroxyacyl dehydrogenase myocardial levels). Pam associated with Dox did not change ventricular function or MMP-2 activity, but it decreased lipid hydroperoxide (p=0.042) and increased catalase (p<0.001) and superoxide dismutase levels (p<0.001). Also, Pam improved phosphofructokinase (p=0.021) and β-hydroxyacyl dehydrogenase levels (p<0.001). Conclusion: Pam attenuated acute Dox-induced cardiotoxicity because it decreased oxidative stress and modulated myocardial energetic metabolism.